2008
DOI: 10.1097/mjt.0b013e3180a72255
|View full text |Cite
|
Sign up to set email alerts
|

Monitored Anesthesia Care With a Combination of Ketamine and Dexmedetomidine During Cardiac Catheterization

Abstract: No specific regimen has been universally accepted as ideal for sedation during cardiac catheterization in infants and children. We evaluated a combination of ketamine and dexmedetomidine for sedation during cardiac catheterization in children with congenital heart disease. The study design included a retrospective analysis of data sheets and hospital records. The protocol for sedation was standardized and data collected prospectively for an ongoing quality assurance project. Heart rate, blood pressure, and oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 33 publications
2
57
0
Order By: Relevance
“…Rare anecdotal cases of cardiovascular collapse have been reported in patients with severe myocardial dysfunction as ketamine's negative inotropic effects may predominate when endogenous catecholamine stores are depleted by chronic stress or illness [13][14][15]. Two previous reports have outlined the use of a combination of dexmedetomidine and ketamine during cardiac catheterization [16,17]. These and other reports of this combination of agents for procedural sedation have outlined several potential benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Rare anecdotal cases of cardiovascular collapse have been reported in patients with severe myocardial dysfunction as ketamine's negative inotropic effects may predominate when endogenous catecholamine stores are depleted by chronic stress or illness [13][14][15]. Two previous reports have outlined the use of a combination of dexmedetomidine and ketamine during cardiac catheterization [16,17]. These and other reports of this combination of agents for procedural sedation have outlined several potential benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The limited effects of dexmedetomidine on respiratory functions makes it an ideal agent for sedation of nonintubated, spontaneously breathing patients during invasive procedures. Several studies have reported the use of dexmedetomidine sedation for PCC patients [4,10,11,16]. Munro et al [11] showed that dexmedetomidine is not effective when used as the sole agent for a painful invasive procedure such as cardiac catheterization.…”
Section: Data Are Presented As Means and Standard Deviationsmentioning
confidence: 99%
“…Other reports have also cited the benefits of this combination for congenital heart disease. 11 The tachycardia and rise in blood pressure caused by ketamine is negated by the dose dependent decrease in heart rate and blood pressure by dexmedetomidine. The later also prevents the undesirable side-effects of ketamine like delusions, hallucination etc.…”
Section: Case Descriptionmentioning
confidence: 99%